(untitled) (Journal of Hama University, 2024)
This clinical trial aimed to evaluate the Skeletal Changes of Modified Twin-Block Appliance with Clear Plates in patients with skeletal class II malocclusion The sample of the current study included 16 patients (7 females and 9 males) who had a class II malocclusion division I associated with a retracted lower jaw, and Available all inclusion criteria of the research, a cephalometric radiograph was taken in central occlusion position and timed in two different times T0 before the start of treatment and T1 after 12 months from the start of treatment, and young patients were included, upper and lower impressions were taken with alginate material in addition to a functional bite with red wax for all patients, then the Dental technician started to cast the impressions and started manufacturing the research device. Skeletal changes were studied before and after treatment through the (web ceph) program. This device consists of a soft clear plate with a thickness of 0.5 mm, on top of which an acrylic block is added that is a biting elevation level causing an anterior displacement of the lower jaw upon closing, similar to the elevation of the bite in the traditional device. The soft plate and the bite-enhancing acryl are pressed with a hard plate of 1 mm thickness. The results of this study showed an improvement in the maxillomandibular relationship, where the value of ANB increased significantly from a statistical point of view in the second time of treatment. This clinical trial showed the effectiveness of Modified Twin-Block Appliance with Clear Plates in bringing about Skeletal changes, as the ANB angle improved by (3.59) degrees.